The Dialectics of Nigeria's Opaque Downstream Oil Sector and the Agency of Fuel Subsidy. - Nwozor, Agaptus; Afolabi, Oladiran; Chidume, Chukwudi Godwin; Okidu, Onjefu; Adedire, Solomon Adebayo (Pertanika Journal of Social Sciences & Humanities, 2024)
This paper draws from qualitative data to examine the opacity of Nigeria's downstream oil sector within the ambit of its fuel subsidy policy. It specifically addresses whether the poor state of Nigeria's refineries is linked to the prebendal benefits associated with the administration of fuel subsidies as well as the correlation between the opacity of Nigeria's downstream oil sector and fuel subsidy. Furthermore, the paper interrogates how fuel importation could be considered a rational option to address domestic needs for refined petroleum products. The paper offers two major interrelated insights: First, it finds that fuel subsidy nurtures the propensity for sabotage, corruption, and money laundering; there tends to be a link between fuel subsidy and the non-functionality of Nigeria's state-owned refineries, and second, the pro-poor justifications for sustaining fuel subsidy is a proxy for continued elite enrichment through the manipulation of the subsidy regime. Overall, the paper highlights the imperative of rethinking the fuel subsidy architecture by rebuilding Nigeria's downstream oil sector, especially the domestic capacity for refining crude oil.